Illocutionary Acts in Jack Ma’s Inspiring Speech in His Graduation at The University of Hongkong - Puji Hariati; Anni Holila Pulungan; Rahmad Husein (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
This study addresses types of illocutionary acts in Jack Ma’s inspiring speech in his graduation at the University of Hongkong. The meaning or the function of an utterance in speech-acts can merely be analyzed based on the acts of illocution made by the speaker. In other words, the hearer will be able to give any responses to the utterances made by the speaker if he or she understands the intention of speaker’s utterances. The research is categorized as descriptive qualitative based on Moleong’s theory (2014:82). It aimed to find the types of illocutionary act performed by Jack Ma’s speech in his graduation at the University of Hongkong, to describe the intended forces of each type of illocutionary act performed in that speech, and to find out the context supported interpretation of meaning in illocutionary acts. The findings indicates that there are 7 types of illocutionary acts such : 0 (0%) for declarative, 58 (62 %) for assertive, 11 (12 %) for expressive, 3 (3 %) for directive, 11 (12 %) for commissive, 4 (4 %) for assertive expressive and 7 (7 %) for assertive directive. It means that most of dominant of illocutionary acts is assertive. And context supported the interpreting of meaning performed illocutionary acts can be mentioned through the participants, the setting or social context of interaction, the topic, and the function. All these explanations guided the audience to catch the truly meaning of a speaker.